Thermochemical properties of binary liquid systems N-alcohol/cyclohexane determined by an acoustic method - BEBEK, K. (Archives of Acoustics, 2000)
The results of ultrasonic and volumetric measurements were used to obtain the excess molar enthalpies for binary liquid mixtures containing cyclohexane, as the common component, and primary aliphatic alcohols (n-propanol, n-butanol and n-pentanol) at 293.15 K. The excess molar enthalpies of those systems are positive in the whole concentrations range and show evidently different concentration dependences. The excess internal pressure of the liquid mixtures, determined in a few different ways, are negative for all the systems. The behaviour of those excesses are discussed in terms of intermolecular interactions in the binaries and the self-association potential of the alcohols.